(untitled) (Argos, 2025)
The purpose of the present article is to analyze the "metatheory dramatic" of the anagnorisis exposed in the Aethiopian Story of Heliodorus (9.24-25), confronting it with the prescriptions of Aristotle in the Poetic about this subject. In my opinion, this analysis would allow to understand the function of the apparently inncesary accumulation of forms of recognition at the end of the novel.